Exploration of the Synergy Between 2D Nanosheets and a Non-2D Filler in Mixed Matrix Membranes for Gas Separation - Shi, Feng; Sun, Junxia; Wang, Jingtao; Liu, Min; Wang, Shaofei; Cao, Xingzhong; Yan, Zhikun; Li, Yifan; Nunes, Suzana P. (Frontiers in Chemistry, 2020)
Dual-filler MMMs have attracted special interests in recent years because of the possibility of producing synergetic effect. This study is aimed at exploring the underlying synergy between 2D nanosheets and a non-2D filler in mixed matrix membranes for gas separation. MXene or GO as typical nanosheet filler is selected to be in pair with a non-2D filler, SiO2 or HNTs, with Pebax as the polymer matrix. In this way, four pairs of binary fillers are designed and the corresponding four groups of MMMs are fabricated. By tuning the mass ratio of binary fillers, synergetic effect is found for each group of MMMs. However, the two 2D fillers found different preferential non-2D partners. GO works better with HNTs than SiO2, while MXene prefers SiO2 to HNTs. To be noted, GO/HNTs renders the membranes the maximum enhancement of CO2 permeability (153%) and CO2/N2 selectivity (72%) compared to Pebax control membrane, while each of them as single filler only brought about very limited enhancement of CO2 separation performance. The possible mechanisms are thoroughly discussed in terms of filler dispersion, nanosheet flexibility, and the tortuosity and connectivity of the surface diffusion pathways along nanosheets.